When People Facing Dementia Choose to Hasten Death: The Landscape of Current Ethical, Legal, Medical, and Social Considerations in the United States - Largent, Emily A. (The Hastings Center report, 2024)
Some individuals facing dementia contemplate hastening their own death: weighing the possibility of living longer with dementia against the alternative of dying sooner but avoiding the later stages of cognitive and functional impairment. This weighing resonates with an ethical and legal consensus in the United States that individuals can voluntarily choose to forgo life-sustaining interventions and also that medical professionals can support these choices even when they will result in an earlier death. For these reasons, whether and how a terminally ill individual can choose to control the timing of their death is a topic that cannot be avoided when considering the dementia trajectory. With a focus on the U.S. context, this landscape review considers the status of provisions that would legally permit people facing dementia to hasten death with appropriate support from medical professionals. This review can be used to plan and guide clinical and legal practitioner discussion and policy development concerning evolving questions not fully covered by existing medical decision-making provisions.